Autocomplete Indonesian Dictionary with Trie and Depth-First Search Algorithm - Aaqila Dhiyaanisafa Goenawan; Abdullah Ammar; Mutiara Persada Pulungan; Desy Komalasari (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2022)
In the current era of technology, the internet provides many conveniences for our daily lives. There are no limitations in accessing the internet, we can even search for information that we do not know through the internet. One of them is by using an electronic dictionary. By using the electronic dictionary the user only needs to enter a keyword and the machine will search for the appropriate data. But when the user finishes entering the word in the search engine, the word is not necessarily found, this makes the electronic dictionary less than optimal in terms of time usage. Therefore, we use the autocomplete feature with the trie data structure and the dfs algorithm in order to shorten the time the user is typing a word, where this feature will display a list of words that the user might mean without having to type the word in full.